Tanglewood Steeplechase, 1963. - (:unkn) unknown (Forsyth County Public Library)
WSJ 4-28-63 p.B1.
Tanglewood Steeplechase, 1963. This was the first year the steeplechase was held at Tanglewood Park. The injured horse had to be put down.
Keywords: Forsyth County (N.C.) -- History -- Pictorial works; Forsyth County (N.C.) -- History -- Sources; Digital Forsyth